Brachybacterium paraconglomeratum Endophthalmitis Postcataract Operation - Kazuhiro Murata; Kenji Ozawa; Hideaki Kawakami; Kiyofumi Mochizuki; Kiyofumi Ohkusu (Case Reports in Ophthalmological Medicine, 2020)
Purpose. To present our findings in a case of delayed-onset postoperative endophthalmitis caused by Brachybacterium paraconglomeratum, a rare organism. Observations. A 57-year-old man presented with epiphora and photophobia 17 weeks after a routine cataract extraction with phacoemulsification and intraocular lens implantation. Because endophthalmitis was suspected to be caused by a low-grade pathogen or fungus, an anterior chamber tap was performed. However, both multiplex PCR and culturing were negative. The patient was treated with topical cefmenoxime, oral minocycline, and subconjunctival injection of vancomycin and ceftazidime, but the intraocular inflammation increased. Then, the anterior chamber was tapped again, and the second PCR amplification and direct sequencing which targeted Actinomycetes detected Brachybacterium paraconglomeratum. This pathogen is uncommon for human infections. He was treated with oral amoxicillin, and his intraocular condition slowly improved. Conclusion. This is the first reported case of an ocular disorder caused by B. paraconglomeratum. We recommend that B. paraconglomeratum be considered in cases of delayed-onset postcataract endophthalmitis.